Interpreting Editorial Intentions in Artificial Intelligence Articles by Science Daily Using Language Attitude Analysis - Mulia, Vilya Lakstian Catra (Politeknik Harapan Bangsa Surakarta, 2023)
The popularity of artificial intelligence (AI) rises as the practice of computer science area especially machine learning that functions like a human brain, self-learning from existing data, gaining experience from previous data, and making predictions. Science Daily, as the scientific website providing press releases of current researches narratively, also concerns on publishing articles about AI. In this research, the article titles about AI were the data collected and analyzed in order to know how Science Daily’s editorial views AI. The researcher also tries to classify possible intentions by the editorial in viewing AI. This research was done qualitatively by using systemic functional linguistics (SFL) approach on appraisal, detailed on attitude system: affect, judgement, and appreciation. The researcher finds the most AI articles were entitled positively, dominantly on appreciation: valuation and judgement: capacity. About the possible editorial’s intentions, the researcher classifies them into AI that offers benefits in facilitating particular uses, enables to gain its use by several options, results product and service, and compares with others.